Zakat As A Stimulus For Creating A Triple Bottom Line In Companies In Indonesia - Chaidir Iswanaji; M. Zidny Nafi' Hasbi; Ipuk Widayanti; Silvia Waning Hiyun Puspita Sari (Isti`dal : Jurnal Studi Hukum Islam, 2023)
Triple bottom line focuses the company’s activities on three pillars, namely economic, social, and environmental. This study aims to explain the implementation of zakat in Indonesia as a stimulus function for the implementation of the triple bottom line in companies. Departing from the many problems in Indonesia the implementation of zakat in Indonesia has not been maximally carried out by companies based on the potential of existing companies. The method use in the research is qualitative descriptive with a literature study approach. The findings of this study state that the role of zakat as a triple-bottom-line stimulus can be carried out by starting with efforts ton increase profits through maximum zakat targets. Then proceed with the distribution of zakat in the form of productive zakat as the implementation of social awareness and environmental care. In the case, the role of zakat can function as the axis of the company’s  triple bottom line implementation to the fullest.